Tantangan dan Peluang Pendidikan Islam di Era Mea - malisi, ali sibram (Transformatif, 2017)
Globalization is a process of integration of the national economies of Nations into a global economic system. Globalization also a cultural process which is characterized by the existence of a tendency of the regions in the world, both geographically as well as physically, being uniform in format of social, cultural, economic, and political. In social life, global process has created a culture of egalitarianism, in triggering the emergence of internationalization of culture, creating economic interdependence in the process of production and marketing, and in the field of political liberalization creates. Although globalization campaigned as the era of the future, a promising era of economic growth will bring globally and global prosperity for all. The challenge of national education is growing. Because in the era of the MEA challenge is one of the free flow of skilled workforce ASEAN cross country. If a resource teacher in Indonesia still covered a variety of flaws at both aspects of the competency, qualification, productivity, and well-being, then they can be marginalized in regional and global competition. To that end, the efforts of professional development teachers need to touch up the most fundamental aspects in a change of their competencies